Cultural Meaning in Tourism: A Typological Analysis of Tourist Experiences in Kampung Wayang - Pinontoan, Nexen Alexandre; Ingkadijaya, Rahmat; Nurbaeti, Nurbaeti; Rachman, Arief Faizal (Institute of Computer Science (IOCS), 2025)
Cultural tourism serves as a dynamic platform for identity negotiation, heritage preservation, and intercultural dialogue, particularly within community-based destinations. Rather than merely observing static cultural artifacts, visitors are increasingly drawn to immersive experiences that allow them to engage with living traditions and co-create meaning alongside local hosts. This study focuses on Kampung Wayang, a cultural enclave situated in Wukirsari, Yogyakarta, where the traditional art of wayang kulit is not only preserved but practiced as an everyday expression of cultural identity. Here, tourists are not passive consumers but active participants in a dialogical process of cultural transmission. The findings highlight that meaning-making in tourism is contingent upon the intensity and authenticity of interaction with cultural agents such as dalangs (puppet masters), artisans, and community storytellers. For instance, those who participated in puppet-making workshops or engaged in discussions about wayang philosophy reported deeper emotional resonance and cognitive insight. This supports theoretical models that posit experience as a co-constructed, affective, and reflective process. Ultimately, the study confirms that immersive participation in cultural production fosters not only aesthetic appreciation but also a profound understanding of embedded social values such as justice, loyalty, and spiritual balance. These findings suggest that cultural villages like Kampung Wayang serve as critical arenas for sustainable tourism, where the visitor experience transcends commodification and becomes a catalyst for mutual understanding and heritage continuity. As such, the village operates as both a site of memory and a space of transformation a place where local culture is not only performed, but also renegotiated through the eyes of its guests